IMPACT OF CASTE ON GENDER INEQUALITY IN EDUCATION - Mithilesh Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
The term "gender inequality in India" refers to the disparities that exist between men and women in India in terms of their health, education, economic standing, and political power. There are a number of different worldwide indices that measure gender inequality, and each of these indices produces a distinct ranking for India based not just on each of these aspects but also on a composite basis. The gender gap and the societal factors that contribute to it have an effect on the sex ratio in India, as well as women’s health, educational achievement, and economic situations throughout their lives. Inequality between the sexes in India is a complex problem that affects both men and women in equal measure. Some people believe that some gender equality initiatives are unfair to males and put them in a worse position. However, when the population of India as a whole is considered, it becomes clear that women are at a significant disadvantage in a number of critical aspects.